Reuse of alum sludge for reducing flocculant addition in water treatment plants - Scalize, Paulo S.; Souza, Leonora M. D.; Albuquerque, Antonio (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
The recycling of water treatment residues (WTR) inside drinking water treatment plants (DWTP) seems to be a good option for reusing this type of waste, as well as for reducing the costs with its disposal off and with the acquisition of treatment chemicals. Therefore, a WTR was reused for auxiliary of the coagulation-flocculation processes for reducing the use of aluminium sulfate (coagulant) in a DWTP. Three series of experiments have been conducted involving three water samples with different turbidity and colour, different WTR samples with different total suspended solids (TSS) concentrations and different aluminium sulfate concentrations. The results showed that WTR can efficiently be used for the removal of turbidity between 21 NTU and 218 NTU and colour between 194 HU and 1509 HU for TSS concentration between 1635 mg/dm3 and 5420 mg/dm3, with better results in the range between 1635 mg/dm3 and 2678 mg/dm3. For higher TSS concentrations, the removal of both parameters decrease because there are excess of organics released to water, which demands the use of more coagulant.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 57-70
Keywords: ochrona środowiska; inżynieria środowiska